Socio-technical innovation bundles for dietary diversity, women’s empowerment, and climate resilience: Findings from the baseline study - Jain, Harsha; Gartaula, Hom Nath; Shivhare, Richa; Nayak, Prakash Kumar; Chadha, Deepali; Johri, Yash; Mukhopadhyay, Prama; Goel, Kritika; Dullo, Anandita; Puskur, Ranjitha (CGIAR System Organization, 2024)
The consequences of global climate change on food security are projected to be far-reaching, with complex dynamics varying across locations and timeframes. In many developing regions, climate change exacerbates ecosystem degradation, increases agricultural risks, and disproportionately affects vulnerable groups. Women, in particular, bear the brunt of these challenges due to gender disparities and social inequalities embedded in agrifood systems (UN Women, 2022). To address these challenges, the CGIAR Initiative on Gender Equality (HER+ Initiative) aims to enhance the climate resilience of vulnerable women in food systems across the global south. The Initiative focuses on improving outcomes in areas such as nutrition, health, food security, poverty, livelihoods, gender equality, climate adaptation, environmental health, and biodiversity.